2005
DOI: 10.1158/0008-5472.can-05-0088
|View full text |Cite
|
Sign up to set email alerts
|

β-Tubulin Mutations Are Associated with Resistance to 2-Methoxyestradiol in MDA-MB-435 Cancer Cells

Abstract: 2-Methoxyestradiol is an estradiol metabolite with significant antiproliferative and antiangiogenic activity independent of estrogen receptor status. To identify a molecular basis for acquired 2-methoxyestradiol resistance, we generated a stable 2-methoxyestradiol-resistant (2ME2R) MDA-MB-435 human cancer cell line by stepwise exposure to increasing 2-methoxyestradiol concentrations. 2ME2R cells maintained in the presence of the drug and W435 cells maintained in the absence of the drug showed 32.34-to 40.07-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…A previous study of breast cancer cells resistant to 2ME2 identified mutations in class I h-tubulin that resulted in amino acid substitutions, D197N and K350N mutations (15). Of interest, the 2ME2-resistant leukemia cells selected in the current study acquired four heterozygous mutations in class I h-tubulin including, D197N and K350N.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…A previous study of breast cancer cells resistant to 2ME2 identified mutations in class I h-tubulin that resulted in amino acid substitutions, D197N and K350N mutations (15). Of interest, the 2ME2-resistant leukemia cells selected in the current study acquired four heterozygous mutations in class I h-tubulin including, D197N and K350N.…”
Section: Discussionmentioning
confidence: 81%
“…5), the 2ME2-resistant cells were hypersensitive to colchicine. In contrast, 2ME2-resistant breast cancer cells that also acquired the D197N mutation were cross-resistant to colchicine and Vinca alkaloids (15). The differences therefore could arise from the carboxamide of asparagine in the form of additional hydrogen-bond interactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations